2019
DOI: 10.1371/journal.pone.0221862
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization-induced uncertainties and impacts of crop management harmonization in a global gridded crop model ensemble

Abstract: Global gridded crop models (GGCMs) combine agronomic or plant growth models with gridded spatial input data to estimate spatially explicit crop yields and agricultural externalities at the global scale. Differences in GGCM outputs arise from the use of different biophysical models, setups, and input data. GGCM ensembles are frequently employed to bracket uncertainties in impact studies without investigating the causes of divergence in outputs. This study explores differences in maize yield estimates from five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 103 publications
(142 reference statements)
0
39
0
1
Order By: Relevance
“…All EPIC-based models use the same core executable (EPICv0810) but differences arise from parameterizations of crop cultivars, soil attributes, soil nutrient cycling, hydrologic processes, and field management. See Folberth et al (72) for additional details and evaluations.…”
Section: [4]mentioning
confidence: 99%
“…All EPIC-based models use the same core executable (EPICv0810) but differences arise from parameterizations of crop cultivars, soil attributes, soil nutrient cycling, hydrologic processes, and field management. See Folberth et al (72) for additional details and evaluations.…”
Section: [4]mentioning
confidence: 99%
“…Understanding crop yield response to a changing climate is critically important, especially as the global food production system will face pressure from increased demand over the next century (Foley et al, 2005;Bodirsky et al, 2015). Climate-related reductions in supply could therefore have severe socioeconomic consequences (e.g., Stevanović et al, 2016;Wiebe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that around 20 % to 45 % of IOD variability could be explained by ENSO depending on the data and the investigated time frame (Saji and Yamagata, 2003;Zhang et al 2015). The nature of this relationship is still debated (Hameed et al, 2018;Stuecker et al, 2017), and determining the influence of ENSO on the IOD and vice versa is not in the scope of this study. However, through the use of multivariate ridge regression, we aim to filter the influence of ENSO from the IOD patterns.…”
Section: Limitations and Way Forwardmentioning
confidence: 88%